The model of persuasive Hajj learning environment - Yusoff, Mohd Fitri; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana (Penerbit UTM Press, 2015)
Hajj is one of five pillars of Islam.Every capable and able-bodied Muslim is obliged to make the pilgrimage to Mecca at least once in their lifetime.Even though comprehensive courses were provided before the pilgrimage particularly in Malaysia, additional learning material is still needed.This is due to the complexity of Hajj procedures comprehension including the practical parts. Multimedia (MM) and virtual environment (VE) technology adaptation seems appropriate to be used for Hajj learning.Nevertheless, to design and develop a Hajj learning procedure application needs thorough preparation to achieve the objectives of use, particularly when it deals with elderly peoples who are not really interested in the technological approach learning.Thus, this paper proposed a model of persuasive Hajj learning environment and the theories usage; covering constructivist, MM principles, persuasive design principle and CTML use.This prototype was developed based on the model, and a heuristic evaluation also has been discussed in the end of topic.The methodology used in this study is an adaptation of the research design used by Vaishnavi and Kuechler in 2008.This paper is hoped to bring ideas and help designers and developers in the future.